A rare anomaly of the Mullerian system: OHVIRA syndrome. Comprehensive literature review and report of seven cases - Bosnali, Oktav; Arabul Aydoğdu, Songül; Moralıoğlu, Serdar; Atcı, Şeyma Nur; Armay, Özlem (Urology Journal, 2026)
Purpose: Müllerian anomalies are rare, and the obstructed hemivagina and ipsilateral renal anomaly/agenesis (OHVIRA) syndrome is the rarest. Its subtle and nonspecific symptoms cause delays in diagnosis, especially in prepuberty. This study aims to remind this rare anomaly and review its symptoms, clinical and radiological findings, and treatment in pre- and post-pubertal girls. Materials and Methods: We conducted a retrospective chart review of cases of OHVIRA syndrome that were diagnosed and treated between May 2018 and June 2024. We evaluated the results and reviewed relevant literature. Results: Seven patients were diagnosed with OHVIRA syndrome during the study period. Two patients were diagnosed in the pre-pubertal period, and all post-pubertal cases, except one, underwent surgery. Five (71%) of the seven patients had left-sided obstructed hemivagina with ipsilateral renal agenesis. Conclusion: OHVIRA syndrome is a rare condition. Its diagnosis and management depend on the patient’s age, symptoms, familiarity with the syndrome, and teamwork. Although a renal anomaly is part of the triad of this syndrome, OHVIRA syndrome often remains undiagnosed during infancy, even in cases of prenatally diagnosed renal agenesis. Screening for OHVIRA syndrome and associated urinary anomalies in cases of renal agenesis, particularly in prepubertal cases, is crucial.